Theory of Mind, Phenomenology, and the Double Empathy Problem - Rizzo, Elisabetta Angela (Journal of NeuroPhilosophy, 2023)
According to some neurocognitive studies, autistic people do not have a theory of mind (ToM); this means that they are unable to interpret the thoughts, beliefs and intentions of others just by observing their behaviour and/or listening to what they say and how they say it. By contrast, researchers from phenomenology claim that autistic people experience issues in earlier forms of intersubjectivity and that in some cases a ToM may be used to compensate for issues in empathy. My purpose is to present both the ToM account, along with its internal accounts (theory-theory, simulation theory, theory of mind mechanism), and an overview of phenomenology, followed by the presentation of some of the phenomenological counterarguments to ToM. Finally, I argue that both the neurocognitive approach and the phenomenological view seem to assume that issues reside in autistic people only and do not take into account the communication gap between autistic people and non-autistic people. As recent studies claim, autistic people are able to understand other autistic people, while they experience difficulties in communication when involved in intersubjective relations with non-autistic people. This mismatch between the two groups has been labelled the double empathy problem, and I propose that ToM and phenomenology may offer their support to this new perspective.